Sharia Economic Law in the Perspective of Anthropology and Sociology - Nursyamsudin, Pebriyana; Arifin, Tajul; Abdal (Zona Law And Public Administration Indonesia, 2024)
Anthropology and sociology of Islamic economic law complement each other in understanding this legal phenomenon. Anthropology helps in understanding cultural contexts and traditions, while sociology helps identify the social and structural factors that influence them. The method used in this article is qualitative method, using literature studies whose sources are from books and journals related to the discussion of anthropology and sociology of Islamic economic law. This study opens opportunities to explore the practice, understanding, and social and cultural implications of Islamic economic law, thus enriching moral and ethical insights in Islamic economics more comprehensively. Therefore, this article tries to provide an overview of the Anthropology and Sociology of Islamic Economic Law